The Effect of Financial Knowledge, Financial Confidence, and Learning Capacity on the Financial Behavior of MSMEs in Pakpak Bharat Regency - Kitti Hanriani Sagala; Wahyuddin Wahyuddin; Nurlela Nurlela; Wardhiah Wardhiah (PT Mattawang Mediatama Solution, 2023)
This study examines the influence of financial knowledge, financial confidence, and learning capacity on the financial behavior of MSMEs in Pakpak Bharat Regency. This study uses primary data obtained by distributing questionnaires to 100 MSME actors in Pakpak Bharat Regency. The data analysis technique used is multiple linear regression analysis consisting of data instrument testing, classical assumption testing, and hypothesis testing. The results indicate that partially financial knowledge, financial confidence, and learning capacity positively and significantly affect financial behavior. Meanwhile, the simultaneous test results reveal that financial knowledge, financial confidence, and learning capacity significantly affect the financial behavior of MSMEs in Pakpak Bharat Regency.